Contamination of Soil and Plant By the Hazaribagh Tannery Industries (Journal of the Asiatic Society of Bangladesh, Science, 2017)
An investigation was made at Hazaribagh Tannery area, comprising about 145 industries in Dhaka Metropolitan area. The analyses of soil and plant samples showed that heavy metals contribute significantly towards environmental contamssination resulting from industrial activities. Concentration of heavy metals (Cr, Zn, Pb, Cd, Mn, Fe and Ni) in soil and plant samples cross the MAC (Maximum allowable concentration) in both wet and dry season. In case of soil sample the highest concentration of Cr (172792 ppm) was found at main disposal point. Chromium, Zn, Pb, Cd, Mn, Fe and Ni concentrations at Hazaribagh plant samples respectively ranged from 171-1348, 247-777, 45-96, 1.66-2.17, 72-231, 354-787, and 18-38 ppm respectively in dry season and 75-1142, 209-691, 29- 84, 1.02-2.00, 66-124, 331-664, 11-37 ppm respectively in wet season. Concentration went down gradually with increasing distance from the main disposal point (spot 1). But again high concentration (150708 ppm of Cr) was noted in spot 6. Similar results were found for plant samples. High concentrations of heavy metals were found in plant samples which consequently affect food chain, which may be a major environmental concern.Asiat. Soc. Bangladesh, Sci. 43(2): 207-222, December 2017